Integration of Local Wisdom and The Existence of Customary Law in Climate Change Mitigation Policies - Sigit Sapto Nugroho; Angga Pramodya Pradhana (Universitas Darunnajah Jakarta, Indonesia, 2026)
This study aims to analyze the integration of local wisdom and the existence of customary law in climate change mitigation policies. The method used is normative juridical with an analytical and philosophical approach, through a review of laws and regulations, scientific literature, and previous research. The results show that local wisdom and customary law have a significant contribution to maintaining ecosystem balance and supporting climate change mitigation policies. However, their integration into policies remains normative and has not been accompanied by strengthening customary institutions. This study also found disharmony between customary law and state law and the challenges of modernization that weaken the existence of traditional values. Therefore, substantive legal recognition, strengthening customary institutions, and a collaborative approach (co-governance) are needed to optimize the role of indigenous communities in inclusive, adaptive, and sustainable climate change mitigation policies.